APPLICATION OF SAYING, SYNONYMS, ANTONYMS, AND INDONESIAN DICTIONARY USING MICROSOFT VISUAL BASIC 6.0 - Agus Budi Setyawan; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2005)
This writing describes the application of the proverb, synonym, antonym, and dictionaries Indonesian. Basically, this application to find out about the meaning of the proverb, synonym, antonym and meaning of the word in Indonesian. For that the author wanted to show them in computerized form using Microsoft Visual Basic 6.0. by presenting it in the form of computerized data that the authors hope that we get a more accurate or  the possibility of error becomes smaller. Also expected this application enriches the used.